Microfluidic manufacturing of surface-functionalized graphene oxide nanoflakes for gene delivery. Issue 6 (23rd January 2019) - Di Santo, Riccardo; Digiacomo, Luca; Palchetti, Sara; Palmieri, Valentina; Perini, Giordano; Pozzi, Daniela; Papi, Massimiliano; Caracciolo, Giulio
Abstract : Microfluidic assembly of graphene oxide nanoflakes and cationic lipids produces surface functionalized hybrid nanoparticles with superior transfection efficiency and no cytotoxicity. Abstract : Graphene oxide (GO) is a single-atomic-layered material made of a sheet of oxidized carbon atoms arranged in a honeycomb structure. Thanks to the notable physical and chemical properties of GO, GO-based nanomaterials have applications in many fields of research, including gene delivery. It has been reported that pristine GO can absorb single-stranded DNA and RNA through π–π stacking, which cannot be used as a gene carrier because it is hard to load double-stranded DNA (dsDNA). To tackle this issue, this work was aimed at developing a hybrid nanoparticle (NP) system made of GO coated with cationic lipids (hereafter referred to as GOCL) with suitable physical–chemical properties for gene delivery applications. To this end, nanosized GO flakes (nGO) were coated with the cationic lipid 1, 2-dioleoyl-3-trimethylammonium-propane (DOTAP) by microfluidic mixing. Comprehensive characterization of GOCL NPs was performed by a combination of dynamic light scattering (DLS), micro-electrophoresis and atom force microscopy (AFM). Our results show that GOCL NPs exhibit adequate size (<150 nm) and surface charge ( ξ = +15 mV) for gene delivery purposes. Complexes made of GOCL NPs and plasmid DNA (pDNA) were used to transfect human cervical cancer cells (HeLa) and human embryonic kidney (HEK-293) cells. Pristine nGO and DOTAP cationic liposomes were used as a reference. GOCL NPs exhibited a similar TE but a much higher cell viability compared with DOTAP cationic liposomes. Confocal fluorescence microscopy provided a reasonable explanation for the superior performance of GOCL/DNA complexes showing that they are much more numerous, regular in size and homogeneously distributed than DOTAP/DNA complexes, thus splitting their gene payload over the entire cell population. Because of the imperative demand for efficient and safe nanocarriers, this study will contribute to the development of novel surface-functionalized GO-based hybrid gene vectors.